The Concept of An Innovative Customer Intelligence Application Supporting the Development of Commercial Enterprises - Agnieszka TOMASZEWICZ (Communications of International Proceedings, 2021)
The use of modern technologies changes the face of the functioning of enterprises, and the emerging new features change the needs and information capabilities of managers. Enterprises should make decisions leading to increased efficiency of their operations, allowing for dynamic interactions with customers. The basis for building the effectiveness of business decisions and a positive perception of the company are analyses of customers and their behavior profiles. In recent years, Customer Intelligence has become helpful in this regard. It creates a group of marketing processes that allow enterprises to plan and design relationships with customers and to interact with them based on data that was previously obtained. The purpose of the article is to present an innovative customer service system that utilizes information and communication technologies, as a way to reach the customer more precisely, identify his/her needs and purchasing behavior, and facilitate the implementation of personal tasks of sales representatives.
Keywords: Modern technologies; Customer Intelligence Application